The Role of PAI Teachers In Optimizing Religious Moderation In Students at SMA Negeri 1 Kendari - DJ, Sitti Marlia Purnama; Abbas; Nourma Yulita (Dirasah: Jurnal Pendidikan Islam, 2026)
This study aims to examine the role and influencing factors of Islamic Religious Education teachers in optimizing religious modernation among students at SMA Negeri 1 Kendari. The research employs a qualitative approach with a field study design. Data sources include the principal, vice principal, students, IRE teachers, and other subject teachers at SMA Negeri 1 Kendari. The research site was selected based on its relevance to the study's criteria. Data collection techniques included observations, interviews, and documentation. Data analysis involved data collection, data reduction, data presentation, and conclusion drawing. The findings reveal that the implementation of religious moderation at SMA Negeri 1 Kendari has been carried out effectively. The roles of IRE teachers include: (a) providing guidance on the implementation of religious moderation values; (b) offering innovative learning strategies to enhance religious moderation; (c) integrating religious moderation values into the curriculum; (d) evaluating the implementation of religious moderation; and (e) serving as role models for students. Factors influencing the optimization of religious moderation at school include supporting factors such as the solidarity among IRE teachers and the entire academic community, school policies like workshops and teacher meetings, and adequate infrastructure including worship facilities for each religion, laboratories, libraries, classrooms, sports fields, auditoriums, teacher rooms, and administration offices. Inhibiting factors include students’ unwise use of technology, such as reliance on Artificial Intelligence (AI), the prevalence of online gaming among students, and the diminishing presence of local content in the curriculum.